Sixteen isolates of group C streptococci taken during outbreak in pigs and monkeys in Bali were examined for their haemaglutination activities using 2% erythrocyte suspension from pigs. Five isolates (31,25%) showed very strong (++) result with geometric titer mean of 22.8, other isolates (31,25%) gave strong (+) results with geometric titer mean of 22 and the remain six isolates (37,5%) showed weak or negative haemagglutination activities. Nonencapsulated bacteria yielded haemagglutination acti - Iwan Harjono Utama; I Ketut Berata; I Gusti Ketut Suarjana; I Nengah Kerta Besung; Agnes Endang Tri H (Media Veteriner, 1999)
Sixteen isolates of group C streptococci taken during outbreak in pigs and monkeys in Bali were examined for their haemaglutination activities using 2% erythrocyte suspension from pigs. Five isolates (31,25%) showed very strong (++) result with geometric titer mean of 22.8, other isolates (31,25%) gave strong (+) results with geometric titer mean of 22 and the remain six isolates (37,5%) showed weak or negative haemagglutination activities. Nonencapsulated bacteria yielded haemagglutination activities stronger than encapsulated. Treatments with heating up to 90 °C, HCl extraction and opsonization reduced haemagglutination titers.